2016
DOI: 10.21675/2357-707x.2016.v7.nesp.687
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos Gerais Da Formação Da Enfermagem: O Perfil Da Formação Dos Enfermeiros Técnicos E Auxiliares

Abstract: O artigo tem como objetivo analisar os aspectos gerais da formação profissional dos trabalhadores da equipe de enfermagem. É um estudo transversal cuja população alvo é constituída por todos os enfermeiros, técnicos e auxiliares de enfermagem do Brasil, que possuem registro ativo no Conselho Federal de Enfermagem (COFEN). Os resultados enfatizam que a formação é realizada principalmente no setor privado e no Sudeste. Mostram ainda, que a maioria concluiu a graduação há menos de 10 anos e em horário parcial. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0
85

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(134 citation statements)
references
References 0 publications
5
41
0
85
Order By: Relevance
“…In a national study conducted to characterize the training of the nursing team, 80.0% of Brazilian nurses did some postgraduate course and 34.3% of nursing assistants and technicians had an undergraduate degree (22) . In the present study, were found higher rates, and 95.8% of nurses and 68.0% of mid-level professionals had an educational level above that required for the position.…”
Section: Discussionmentioning
confidence: 99%
“…In a national study conducted to characterize the training of the nursing team, 80.0% of Brazilian nurses did some postgraduate course and 34.3% of nursing assistants and technicians had an undergraduate degree (22) . In the present study, were found higher rates, and 95.8% of nurses and 68.0% of mid-level professionals had an educational level above that required for the position.…”
Section: Discussionmentioning
confidence: 99%
“…8 These data are confirmed by a national survey, where the results point to the hegemony of the Southeast Region as a hotbed for training and allocation: the total number of nurses registered in the professional department, about 45% have graduated and work in this region. 10 All the 16 courses offer 2,110 job opportunity per year, an average of 132 vacancies per course, and the average of completion is 84%, n other words, the total number of vacancies offered, 16% are idle. According to the legal law, the average annual vacancies and completion is 230, 68.8% are private, and 73 and 99.5% are among the public vacancies.…”
Section: Characterization Of the Coursesmentioning
confidence: 99%
“…Ademais, na educação, é necessário considerar o contexto do indivíduo e do meio em que ele vive (21) . Logo, percebe-se deste modo o papel da educação como instrumento operativo para o desenvolvimento social (22) . Assegurado isso, a formação profissional deve se constituir por habilidades e competências para a atuação em determinantes do processo saúde-doença e senso de responsabilidade social, considerando as diversidades das populações da Amazônia.…”
Section: Resultsunclassified